Peningkatan Hasil Belajar Keterampilan Tendangan Sabit Pencak Silat Peserta Didik Fase C Melalui Model Problem Based Learning - Syayyadi, Achmad; Rahman, Taufik; Nuraisyah, Winda (MAN Insan Cendekia Jambi, 2025)
This study aims to determine the achievement of learning outcomes for crescent kick skills in pencak silat through the application of the model.Problem Based Learningfor PHASE C students (grade 6)SDN Romben Rana 571, Dungkek District, Sumenep Regencyacademic year 2024–2025. The method used isclassroom action researchwith a cycle approach that includes the stages of observation and reflection. Based on the results of the analysis at the pre-cycle stage or initial observation, it is known that only 6 out of 16 students (38%) achieved completion, while 10 students (63%) have not completed. In cycle 1 there was an increase, where 12 students (75%) achieved completion and 4 students (25%) had not. Then in cycle 2, learning outcomes showed a very significant increase, with all students (100%) successfully achieving completion. From these findings it can be concluded that the implementation ofmodel Problem Based Learningeffective in improving learning outcomes of straight kick skills in pencak silat.